Influence of graphene oxide on crystallite size, lattice strain, and porosity in FeGaInS4/PVA composites - Addayeva, Zeynab; Muradov, Mustafa; Filiz, Bilge Coskuner; Baghirov, Mahammad Baghir (IOP Publishing Ltd, 2025)
Polyvinyl alcohol (PVA) nanocomposites reinforced with FeGaInS4 and graphene oxide (GO) were investigated to enhance their structural and morphological properties for advanced functional applications. This work aims to understand how two different two-dimensional layered fillers influence the polymer composite's structure, morphology, and potential application in optoelectronics and energy storage devices. The nanocomposites were synthesized using a solution-casting method and characterized by x-ray diffraction, Fourier-transform infrared spectroscopy, Raman spectroscopy, and field-emission scanning electron microscopy. The incorporation of FeGaInS4 reduced the crystallite size from similar to 30 nm to similar to 8 nm and shifted the microstrain from tensile (0.34 x 10(-6)) to compressive (-17 x 10(-6)), indicating enhanced structural compaction due to polymer-filler interactions. Subsequent addition of GO at 1 wt.% and 3 wt.% further modified the strain to -10.28 x 10(-6) and -6.47 x 10(-6), respectively, attributed to improved interfacial bonding and stress relaxation. GO also decreased defect density and increased porosity by disrupting the PVA network. These synergistic effects between FeGaInS4 and GO demonstrate the tunability of the nanocomposite structure, offering a pathway for tailored materials in optoelectronic and energy storage applications.
Keywords: PVA; FeGaInS4; graphene oxide; crystallite size; lattice strain; OPTICAL-PROPERTIES; REINFORCEMENT; ALCOHOL; Materials Science